The Influence Of Organizational Culture, Job Stress, And Job Satisfaction On Employee Performance At The Medan Polonia Pratama Tax Services Office - Sunarya Sunarya; M. Khairul Imam Sadly; Lena Melyana Hasibuan; Nelly Agustini Simanjuntak; Sri Gustina Pane; Eddi Suprayitno (Economics and Digital Business Review, 2024)
The purpose of this study is to ascertain how employee performance at the Medan Polonia Pratama Tax Service Office is affected by organizational culture, stress at work, and job satisfaction in part and simultaneously. The exploration was directed at the Medan Polonia Pratama Expense Administration Office, Jalan Sukamulia No. 17A Medan, with a population of 111 individuals and an examination test of 53 individuals. Information assortment was completed through meetings, polls and documentation. The information investigation method utilized is numerous relapse examinations involving the IMB Insights for Item and Administration Arrangement (SPSS) PC program variant 25. In view of the consequences of the examination, it is found that hierarchical culture significantly affects the presentation of workers in the Medan Polonia Pratama Duty Administration Office. This is upheld by the outcomes t count > t-table investigation (5.814 > 2.010) at n = 53 at the 95% importance level. Work pressure affects the exhibition of Medan Polonia Pratama Duty Administration Office representatives; this is upheld by the t count < t-table examination (0.577 < 2.010) at n = 53 at an importance level of 95%. Work fulfillment affects the exhibition of representatives of the Medan Polonia Pratama Expense Administration Office; this is upheld by the investigation of t count < t-table (2.381 > 2.010) at n = 53 with an importance level of 95%. The F-count esteem > F table (38.974 > 2.79) expresses that there is a positive and critical impact of hierarchical culture, work pressure and occupation fulfillment on the presentation of Medan Polonia Essential Expense Administration representatives.